Key features and differences between industry 5.0 and industry 4.0 - Gurin, D. (НУ «Запорізька політехніка», 2024)
Industrial revolutions play a key role in shaping modern society and its economy. With each new stage of technological change, industry has undergone significant transformations that have affected not only production processes but also society as a whole. In the 21st century, these changes have become more dynamic, and we are gradually moving from Industry 4.0 to Industry 5.0. But what is this new industrial revolution and what are its differences from the previous one? This article analyzes the concepts of Industry 4.0 and 5.0, their key differences, technological innovations, and the impact on the human factor and the global economy. Industry 4.0, or the fourth industrial revolution, is a concept that involves the integration of cyber-physical systems into production processes. The main components of Industry 4.0 are the Internet of Things (IoT), big data, artificial intelligence (AI), autonomous systems, robotics, and automation. Industry 4.0 aims to create smart factories where machines, systems and people work together to optimize productivity and reduce costs
Keywords: Mobile Robot; Manufacturing Innovation; Industrial Innovation